High Temperature Inhibits Ascorbate Recycling and Light Stimulation of the Ascorbate Pool in Tomato despite Increased Expression of Biosynthesis Genes - Massot, Capucine (Public Library of Science, 2013)
Understanding how the fruit microclimate affects ascorbate (AsA) biosynthesis, oxidation and recycling is a great challenge in improving fruit nutritional quality. For this purpose, tomatoes at breaker stage were harvested and placed in controlled environment conditions at different temperatures (12, 17, 23, 27 and 31°C) and irradiance regimes (darkness or 150 µmol m(-2) s(-1)). Fruit pericarp tissue was used to assay ascorbate, glutathione, enzymes related to oxidative stress and the AsA/glutathione cycle and follow the expression of genes coding for 5 enzymes of the AsA biosynthesis pathway (GME, VTC2, GPP, L-GalDH, GLDH). The AsA pool size in pericarp tissue was significantly higher under light at temperatures below 27°C. In addition, light promoted glutathione accumulation at low and high temperatures. At 12°C, increased AsA content was correlated with the enhanced expression of all genes of the biosynthesis pathway studied, combined with higher DHAR and MDHAR activities and increased enzymatic activities related to oxidative stress (CAT and APX). In contrast, at 31°C, MDHAR and GR activities were significantly reduced under light indicating that enzymes of the AsA/glutathione cycle may limit AsA recycling and pool size in fruit pericarp, despite enhanced expression of genes coding for AsA biosynthesis enzymes. In conclusion, this study confirms the important role of fruit microclimate in the regulation of fruit pericarp AsA content, as under oxidative conditions (12°C, light) total fruit pericarp AsA content increased up to 71%. Moreover, it reveals that light and temperature interact to regulate both AsA biosynthesis gene expression in tomato fruits and AsA oxidation and recycling.